Assessing the effectiveness of the right to food in the context of economic globalisation: The case of Mali in West Africa - Diabaté, Alhousseini; Diallo, Boubacar Sidi (Przegląd Prawa Rolnego, 2025)
The research aimed to critically examine the effectiveness of the right to food in West Africa in the context of economic globalisation. It also sought to analyse the influence of market-driven policies, international trade regulations and domestic legal frameworks on food security, with a particular focus on Mali. Despite the anticipated benefits of globalisation, food insecurity remains a significant challenge in West Africa, characterised by widespread hunger and human suffering. This situation has been exacerbated by prevailing land and food governance models influenced by liberal trade policies and legal frameworks that prioritise market interests over social needs. The current market-oriented paradigm undermines local livelihoods and compromises prospects for sustainable development. Given the severity of the crisis, urgent interventions are required. Where it is not feasible to shield key resources such as land and food completely from market forces, it is crucial to strike a balance between economic objectives and social welfare in order to enhance food security for vulnerable populations.